Efficacy and safety of topical delgocitinib in patients with chronic hand eczema: data from a randomized, double‐blind, vehicle‐controlled phase IIa study. (8th November 2019) - Worm, M.; Bauer, A.; Elsner, P.; Mahler, V.; Molin, S.; Nielsen, T.S.S.
Summary: Background: Management of chronic hand eczema (CHE) remains a challenge; effective topical treatment is limited to corticosteroids. Objectives: To assess the efficacy and safety of a novel, pan‐Janus kinase inhibitor (delgocitinib) in patients with CHE. Methods: In this randomized, double‐blind, phase IIa study, patients with CHE received delgocitinib ointment 30 mg g −1 or vehicle ointment for 8 weeks. The primary end point was the proportion of patients achieving treatment success ['clear'/'almost clear' skin with ≥ 2‐point improvement in the Physician's Global Assessment of disease severity (PGA)] at week 8. Secondary end points included Hand Eczema Severity Index (HECSI) score changes and the proportion of patients achieving treatment success on the Patient's Global Assessment of disease severity (PaGA). Results: Ninety‐one patients were randomized. More patients receiving delgocitinib (46%) than vehicle (15%) [odds ratio 4·89, 95% confidence interval (CI) 1·49–16·09; P = 0·009] achieved treatment success (PGA). Adjusted mean HECSI score at week 8 was lower with delgocitinib (13·0) than with vehicle (25·8) (adjusted mean difference −12·88, 95% CI −21·47 to −4·30; P = 0·003). More patients receiving delgocitinib than vehicle achieved treatment success by PaGA, but this did not reach statistical significance. The incidence of adverse events was similar with delgocitinib and vehicle; none led to discontinuation of delgocitinib. Conclusions: Delgocitinib ointment was efficacious and well tolerated. As a plateau of efficacy was not observed, a longer treatment period may lead to increased efficacy. Further clinical studies are warranted to confirm these findings in patients with CHE. What's already known about this topic? Chronic hand eczema (CHE) has a significant burden. Few randomized controlled studies have evaluated current treatments for CHE; only limited data are available to inform and guide clinical practice decisions. There is currently an unmet need for efficacious and well‐tolerated topical treatment options for patients with CHE. What does this study add? Delgocitinib is a novel, pan‐Janus kinase (JAK) inhibitor specific for JAK1, JAK2, JAK3 and tyrosine kinase 2. Topical use of delgocitinib ointment resulted in clearance of CHE after 8 weeks of treatment in a significantly greater number of patients than vehicle; delgocitinib was also well tolerated. Results from this proof‐of‐concept clinical study suggest that topical delgocitinib may provide therapeutic benefit to patients with CHE with inadequate responses to topical corticosteroids. Abstract : Linked Comment: Strowd and Feldman. Br J Dermatol 2020; 182:1078 .